The Effect of Ethics and Work Environment on Loyalty Through Employee Satisfaction and Commitment - Bambang Hadi Santoso Dwidjosumarno (Faculty of Economics and Business Udayana University, 2021)
This study aims to prove whether work ethics and work environment variables significantly influence employee loyalty through job satisfaction and employee commitment to Nurul Hayat Surabaya employees. Data collection in this study used a questionnaire with a total sample of 75 employees at the Nurul Hayat Surabaya Foundation. Criteria for respondents in this study were employees of the Nurul Hayat Surabaya foundation who had worked more than one year. Sampling uses Non Probability Sampling with saturated sampling technique or often also called a census. This research uses a quantitative approach with SEM Partial Least Squares analysis method. Exogenous variables in this study are work ethics and work environment, mediating variables used are employee satisfaction and commitment, while the endogenous variables used are employee loyalty. The findings of this study indicate that the intervening variable, namely job satisfaction, does not significantly influence endogenous variables, namely the employee loyalty of the Nurul Hayat Foundation in Surabaya and employee commitment has a significant effect on the endogenous variable, namely the employee loyalty of the Nurul Hayat Foundation in Surabaya. Exogenous variables of work ethics and work environment have a significant effect on endogenous variables, namely employee loyalty of Nurul Hayat Foundation, Surabaya. Suggestions for further research are expected to increase the scope of research subjects with the same characteristics of respondents.